The Virtual Laboratory Learning Environment: VLLE on Metaverse for University in Thailand - Chatwattana, Pinanta; Saisong, Pischa; Rojanapasnichwong, Kannikar; Khiankhokkruad, Wichittra (International Journal of Engineering Pedagogy (iJEP), 2023)
The virtual laboratory learning environment on metaverse, or VLLE on metaverse, is a kind of learning media in the virtual world, which can be accessed through a virtual laboratory in the form of metaverse. To enter VLLE on metaverse, users must simulate themselves in the form of 3D avatar, and then they are able to perform any tasks and interact with any objects or surrounding environments therein, which are all virtual images. The study question of this research focuses on the steps and methods related to the development of media for use in VLLE on metaverse and on what design features are satisfactory and would be well accepted by participants. In this study, the researchers have applied concepts and new teaching innovations that correspond to the current situations and can support the learning formats that can be done anywhere and anytime. This practice is believed to promote self-directed learning experiences and other skills while allowing students to evaluate their activities on their own as well. The research results are in line with the researchers’ expectations: it was found that VLLE on metaverse can be used as a public interaction tool through mobile applications for the university population and the general public outside. This is because new technologies have been developed and employed in the media and the existing technologies in such a way that an environment close to the real learning conditions can be produced, which can create a learning society without borders.